Trends of ‘urolithiasis: interventions, simulation, and laser technology’ over the last 16 years (2000–2015) as published in the literature (PubMed): a systematic review from European section of Uro-technology (ESUT) - Pietropaolo, Amelia; Proietti, Silvia; Geraghty, Rob; Skolarikos, Andreas; Papatsoris, Athanasios; Liatsikos, Evangelos; Somani, Bhaskar K. (World journal of urology, 2017)
Purpose To look at the bibliometric publication trends on ‘Urolithiasis’ and aspects of treatment and training associated with it over a period of 16 years from 2000 to 2015. To this end, we conducted this study to look at the publication trends associated with urolithiasis, including the use of simulation, laser technology, and all types of interventions for it. Materials and methods We performed a systematic review of the literature using PubMed over the last 16 years, from January 2000 to December 2015 for all published papers on ‘Urolithiasis’. While there were no language restrictions, English language articles and all non-English language papers with published English abstracts were also included. Case reports, animal and laboratory studies, and those studies that did not have a published abstract were excluded from our analysis. We also analyzed the data in two time periods, period-1 (2000–2007) and period-2 (2008–2015). Results During the last 16 years, a total of 5343 papers were published on ‘Urolithiasis’, including 4787 in English language and 556 in non-English language. This included papers on URS ( n = 1200), PCNL ( n = 1715), SWL ( n = 887), open stone surgery ( n = 87), laparoscopic stone surgery ( n = 209), pyelolithotomy ( n = 35), simulation in Endourology ( n = 82), and use of laser for stone surgery ( n = 406). When comparing the two time periods, during period 2, the change was +171% ( p = 0.007), +279% ( p < 0.001), and −17% ( p = 0.2) for URS, PCNL, and SWL, respectively. While there was a rise in laparoscopic surgery (+116%), it decreased for open stone surgery (−11%) and pyelolithotomy (−47%). A total of 82 papers have been published on simulation for stone surgery including 48 papers for URS (67% rise in period-2, p = 0.007), and 34 papers for PCNL (480% rise in period-2, p < 0.001). A rising trend for the use of laser was also seen in period 2 (increase of 126%, p < 0.02, from 124 papers to 281 papers). Conclusions Published papers on intervention for Urolithiasis have risen over the last 16 years. While there has been a steep rise of URS and minimally invasive PCNL techniques, SWL and open surgery have shown a slight decline over this period. A similar increase has also been seen for the use of simulation and lasers in Endourology.